2023
DOI: 10.1021/acsami.2c21792
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the Interplay at the Buried Interface for Efficient and Stable Carbon-Based CsPbI2Br Perovskite Solar Cells

Abstract: Buried interface modification is promising for preparing high-performance perovskite solar cells (PSCs) by improving the film quality and adjusting the interfacial energy level alignment. In this work, multifunctional ethylenediaminetetraacetic acid diammonium (EAD)-modulated ZnO is employed as an effective buried interface to regulate the interplay between SnO2 and CsPbI2Br in carbon-based inorganic PSCs (C-IPSCs). The burying of EAD into the ZnO interlayer not only enhances the photoelectric properties of Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Therefore, a small amount of dphase has little effect on the E g of CsPbI 2 Br, which is consistent with previous reports. 5,20,[74][75][76][77] In contrast, the perovskite lms on the doped ZnO lms presented a mitigated variation trend in the lm color and absorption spectra under the same conditions, suggesting inhibited moisture-induced phase degradation, as further conrmed by the temporal evolution of XRD patterns (Fig. 6a-d).…”
Section: Resultsmentioning
confidence: 95%
“…Therefore, a small amount of dphase has little effect on the E g of CsPbI 2 Br, which is consistent with previous reports. 5,20,[74][75][76][77] In contrast, the perovskite lms on the doped ZnO lms presented a mitigated variation trend in the lm color and absorption spectra under the same conditions, suggesting inhibited moisture-induced phase degradation, as further conrmed by the temporal evolution of XRD patterns (Fig. 6a-d).…”
Section: Resultsmentioning
confidence: 95%
“…The crystallinity of the 2D/3D perovskite films was examined through X-ray diffraction (XRD) measurements. As depicted in Figure b, all the films exhibited typical diffraction peaks at 14.4°, 20.7°, and 29.5°, corresponding to the (100), (110), and (200) planes of CsPbI 2 Br, respectively . No significant changes were observed in the XRD patterns after the post-treatment with the BAI/ACN and BAI/IPA solutions, indicating that the 3D to 2D transformation on the surface could hardly affect the crystallinity of 3D perovskite.…”
Section: Results and Discussionmentioning
confidence: 96%
“…With the goal of improving the crystallization process of the perovskite active layer, Huang et al demonstrated the positive role of EACl in regulating this process by introducing it into the Sn-based perovskite layer. [182] Concurrently, Cl À ions from the perovskite crystal lattice primarily distribute on the surface and interfaces of the perovskite, resulting in defect passivation and further resistance to oxidation. A small number of Cl À ions enter the perovskite lattice due to their small size and positive charge, enhancing device performance and achieving a PCE of 12.50%.…”
Section: Lead-free Pscsmentioning
confidence: 99%